n-Channel Organic Thin-Film Transistors based on Naphthalene-Bis(dicarboximide) Polymer for Organic Transistor Memory Using Hole-Acceptor Layer - Khairul Anuar Mohamad; Ismail Saad; Hisashi Fukuda (Japanese Journal of Applied Physics, 2012)
Organic semiconductors have been the subject of interest for the past decade. Despite significant progress in the p-channel organic thin-film transistors (OTFTs), there are still problems concerning the development of n-channel OTFTs owing to the selection of n-channel organic materials, which are limited to a very small number of molecules and polymers [1], and also serious drawbacks, including poor solubility, difficulty of synthesis and unstable transistor operation under ambient atmosphere [2]. Since the first air-stable n-channel OTFTs based on naphthalenetetracarboxylic diimides was reported [3], a large number of n-channel organic materials have been based on either naphthalene diimide (NDI) — or perylene diimide (PDI)-based polymers. It is therefore clear that n-channel organic materials have an important role in the continuing development of organic-based circuits and products. In this study, we focused to elucidate the fabrication and characterization of n-channel OTFTs based on poly{[N, N'bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5'-(2,2'-bithiophene)} [P(NDI2D-T2)]. Moreover, we also demonstrate organic transistor memory with an n-channel P(NDI2OD-T2) OTFTs using poly(3-hexylthiophene) (P3HT) as the charge trapping layer.